The grand tour: Keynes and Goodwin go to Greece - Eduardo Amaral Haddad; Natalia Cotarelli; Thiago Cavalcante Simonato; Vinicius de Almeida Vale; Jaqueline Coelho Visentin (Journal of Economic Structures, 2020)
The impact of the crisis in the Greek economy was not uniform among the regions, threatening socioeconomic cohesion. In this paper, we explore the concept of the income multiplier in a multi-regional input-output setting, in the context of the Greek recession, showing empirical evidence for the increasing magnitude of the multiplier during the recession period. The main results reveal a complex system of interregional relations on some of whose structural characteristics the cyclical reaction paths of the regions depends. In this case, the use of fiscal instruments to stimulate local activity in the regions may bring about important implications for regional inequality in Greece.
Keywords: E12; E62; R11; 330; Interregional input-output analysis; Keynesian multiplier; Recessions; Greece; Austerity policy; Countercyclical regional policy